Inside Cover: Arylation of N‐Methyl‐2‐oxindole with Arylboronic Acids in Water Catalyzed by Palladium(II) Pincer Complexes with a Low Catalyst Loading (ChemCatChem 6/2017). Issue 6 (7th March 2017) - Vignesh, Arumugam; Kaminsky, Werner; Dharmaraj, Nallasamy
Abstract : The Cover shows a Pd II ONO pincer complex that efficiently catalyzes the site‐selective C3‐arylation of N ‐methyl‐2‐oxindole with arylboronic acids at room temperature in aqueous media.In their Communication, A. Vignesh et al. demonstrate that this synthesis of 3‐aryl‐N‐methyl‐2‐oxindoles proceeds efficiently with low catalyst loading (0.01 mol %), using two new Pd II ONO pincer complexes as homogeneous catalysts. The catalysts showed good compatibility with a wide range of substrates and no appreciable loss of yield was observed in the recyclability tests in up to five consecutive runs.